Investigating telemedicine approaches: a 10-country comparison - Abd Ghani, Mohd Khanapi; A Mostafa, Salama; Mustapha, Aida; Aman, Hannani; Mohamed, Mazin Abed; Jaber, Mustafa Musa
This paper investigates and appraises the current state of knowledge and practice and the existing telemedicine approaches in ten countries, namely China, Taiwan, Hong Kong, Singapore, Japan, South Korea, Canada, the U.K, Australia and New Zealand. The literature dealing with telemedicine development approaches was reviewed, compared and contrasted between Malaysia and the 10- country. Based on our analysis results, the suitable approaches and technologies were discussed. If no suitable approach is found, it will be possible to elicit the most relevant approach and best practice and to learn from any possible weaknesses.